2017
DOI: 10.1515/nanoph-2017-0019
|View full text |Cite
|
Sign up to set email alerts
|

Unidirectional reflectionless light propagation at exceptional points

Abstract: Abstract:In this paper, we provide a comprehensive review of unidirectional reflectionless light propagation in photonic devices at exceptional points (EPs). EPs, which are branch point singularities of the spectrum, associated with the coalescence of both eigenvalues and corresponding eigenstates, lead to interesting phenomena, such as level repulsion and crossing, bifurcation, chaos, and phase transitions in open quantum systems described by non-Hermitian Hamiltonians. Recently, it was shown that judiciously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
60
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(65 citation statements)
references
References 148 publications
(181 reference statements)
0
60
0
Order By: Relevance
“…Many interesting wave phenomena have been observed on PT -symmetric optical structures. Noticeable examples include unidirectional reflectionless propagation [5][6][7][8][9][10][11][12][13][14][15][16][17], single-mode lasing [18,19], and simultaneous lasing and coherent perfect absorption [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Many interesting wave phenomena have been observed on PT -symmetric optical structures. Noticeable examples include unidirectional reflectionless propagation [5][6][7][8][9][10][11][12][13][14][15][16][17], single-mode lasing [18,19], and simultaneous lasing and coherent perfect absorption [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…By using Rydberg states [33,34] we can introduce interactions between the excitations and study the many-body effect in flux lattices [35]. An interesting connection of our results can also be made to the unidirectional reflectionless (invisible) photonic structures [36][37][38][39], such as the paritytime symmetric materials [40]. We have observed that under certain conditions one of the two reflectivities is nearly zero while the other is big.…”
mentioning
confidence: 62%
“…In particular, as concerns solitons, although P T -symmetric systems belong to the class of dissipative ones, where solitons generally exist as isolated attractors, selected by the condition of the double balance between the dispersion (or diffraction) and nonlinearity, and between the gain and loss (the latter principle is very important for the creation of stable temporal solitons in fiber lasers [102]), in P T -symmetric systems solitons exist in continuous families, similar to their counterparts in conservative models [100,101]. In addition to the interest to fundamental studies, systems with the P T symmetry offer promising applications, such as "light diodes", admitting unidirectional propagation of light in the waveguide, and lasers operating in the P T -symmetric regime [103].…”
Section: Dissipative and Parity-time Symmetric Waveguidesmentioning
confidence: 99%